Maternal offspring behaviour in curraleiro pé duro naturalized cattle in brazil - Castanheira, Marlos (2013)
The objective of the present study consisted of describing dam and calf suckling behaviour of Curraleiro Pé Duro cattle. In this study, 38 mother-offspring pairs and one mother-offspring-orphan trio were observed for 10 hours daily during three consecutive days spaced every four months over a period of one year. After identification,theanimalswereobserved under field conditions where calf posture and the number of sucklingepisodes(NS),meansucklingduration(MSD),total suckling duration per day (TSD) as well as natural weaning of these animals were recorded. The model assessed the effects of calf sex and age as well as feeding time. Suckling episodes (70.6%) had a duration of one to five minutes and the calf that suckled in the inverted parallel position had greater chances of success during suckling (99.5%); the younger animals had a shorter mean suckling duration (4.0±0.6 minutes) than the older ones (7.5±1.2 minutes) but they showed a higher number of suckling episodes (6.29±1.00 vs. 1.33±0.04 feeds in 10 hours for young and older calves). Only the factor age in the firstthree months was significant for NS,MSD,and TSD;males and females had similar suckling episode length and distribution. While these animals show some traits similar to other cattle breeds such as feeding their calves early in the morning and late in the afternoon, the dams spend large periods of the day away from their calves and suckling is more frequent but for shorter periods of time compared with other breeds. Other unique features such as allo-suckling and formation of day-long crèches are observed in this breed. © 2013 Sociedade Brasileira de Zootecnia;.